8 - Employment status, medical support and Income as significant factors in Access to Essential Medicines - Chinwe Christopher Obuaku-Igwe (African Sociological Review, 2017)
Poor affordability (as a constraint to access to essential medicine) or lack of capacity to pay for essential medicines has been associated more often with unemployed persons or low-income earners. Even though there is a growing body of work on access to essential medicines in Nigeria, no study has been conducted to determine the extent to which affordability varies across and within social groups. Using six variables, this paper examines factors that have an impact on essential medicine in Nassarawa state, Nigeria. It asks the question: in what ways does the ability to purchase medicines depend on income, perceived unreasonable burden, age, gender, medical aid and employment status? 1000 subjects who utilized primary healthcare facility were randomly selected for the study. A standardized questionnaire was used to determine how the burden of purchasing essential medicines varied across employment and income groups. Out of the 1000 subjects, 640 were females; 360 males with a mean age of 37.4 and a response rate of 90%. Results: Two factors: ‘employment status and perceived unreasonable burden’ were significant predictors of affordability (F (6,993) = 260.052092, P =.05, R2 = .611, employment status= P <0.03 and burden= P <0.03). There was evidence to support that an individual’s employment status has an effect on their ability to pay for essential medicine or treatment. There were significant differences in affordability between individuals who had full time paid employment and those who were either self-employed or without a fulltime paid employment, if all factors are constant. Affordability coefficient increased by .35 for each income unit. In addition, there were significant differences that bothered on the type of employment (paid employment vs selfemployed, part time vs fulltime), membership of a medical aid and the number of people in the household (Cohen’s d = (333.3 - 660) ⁄ 350.4283 = 0.932288.) Conclusion: “Affordability” or the ability to pay for treatment, varied across and within employment groups (status), an indication that greater access to essential medicine was found to be correlated with fulltime paid employment and medical aid.